The cooperative model in the Philippine Social Economy contributions and challenges of three local cooperatives - Salonga, Norby Roque
This study emphasizes the transactional and transformational roles of the cooperative model in the Philippine social economy. Cooperative as a segment of social entrepreneurship provides more opportunities for its stakeholders to be actively involved in transactional and transformational activities. Its crucial feature on equitable distribution of resources in the form of income and patronage refunds clarifies its impact on the economy and society. The ownership structure is inclusive because it allows members to have equitable access to the programs and services of the cooperative and practice leadership. Therefore, the model increases the level and quality of participation among members and creates a culture of shared prosperity and accountability.